2003
DOI: 10.2113/gscanmin.41.3.727
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Minerals in the Xihuashan Y-Enriched Granitic Complex, Southern China: A Record of Magmatic and Hydrothermal Stages of Evolution

Abstract: The Xihuashan granitic complex (southern China) is mainly composed of coarse-grained porphyritic biotite granite (G-a), medium-grained porphyritic biotite granite (G-b), and medium-to fine-grained porphyritic biotite granite (G-c). The G-a granite is characterized by monazite-(Ce) and xenotime-(Y), in addition to commonly observed zircon and uranoan thorite. In the G-b and G-c intrusive units, monazite-(Ce) becomes very scarce, whereas Y-bearing minerals, including Y-bearing spessartine, xenotime-(Y), gadolini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 31 publications
3
27
0
2
Order By: Relevance
“…Xenotime is observed throughout the Xihuasan complex. Wang et al [37] suggested that xenotime crystallized at the magmatic stage and experienced further evolution at the late-magmatic and hydrothermal stage. Xenotimes from G-1, G-2, G-3 and G-5 granites were separated for U-Pb dating in this study.…”
Section: Xihuashan Granite In Southern Chinamentioning
confidence: 99%
“…Xenotime is observed throughout the Xihuasan complex. Wang et al [37] suggested that xenotime crystallized at the magmatic stage and experienced further evolution at the late-magmatic and hydrothermal stage. Xenotimes from G-1, G-2, G-3 and G-5 granites were separated for U-Pb dating in this study.…”
Section: Xihuashan Granite In Southern Chinamentioning
confidence: 99%
“…Furthermore, the association of Y-poor fluorite and synchysite-(Y) in the aplite-pegmatite of Jabal Sayid may suggest a genetic relationship between the two minerals. Wang et al (2003) reported alteration of yttrian fluorite in fluid rich environment to fluorite and synchysite-(Y) according to the following reaction:…”
Section: Discussionmentioning
confidence: 99%
“…Such late hydrothermal variety was described as fluorite III at Mt. Ploskaya (Voloshin and Pakhomovsky, 1986) and noted at the Kutessai (Zuev and Kosterin, 1960), Katugin (Arkhangel'skaya, 1970), and Xihuashan (Wang et al, 2003) deposits. These findings coupled with data on the synthesis conditions show that incorporation of substantial amounts of REE into fluorite at the late, low-temperature stage of natural hydrothermal process is hampered.…”
Section: Structure and Formula Of Tveitite-(y)mentioning
confidence: 96%
“…The best-known occurrences of the mineral are known from Norway, including Tysfjord, Nordland; Iveland, Aust-Agder; and Tørdal, Telemark (Vogt, 1911;Sverdrup, 1968;Neumann, 1985). Yttrofluorite was described from alkaline metasomatized granitic rocks at the Kutessai and Aktyuz deposits in Kyrgyzstan (Zuev and Kosterin, 1960); alkali granitic pegmatite in Pikes Peak, Colorado, United States (Haynes, 1965); Suishoyama and Fukushima, Japan (Uetani et al, 1968); and Y-enriched granite in Xihuashan, Jiangxi, China (Wang et al, 2003). Yttrofluorite is known in Russia as well.…”
Section: Tveitite-(y) and Ree-enriched Fluorite From Amazonitementioning
confidence: 99%